1991
DOI: 10.1182/blood.v78.4.1041.1041
|View full text |Cite
|
Sign up to set email alerts
|

Defective lymphokine-activated killer cell generation and activity in acute leukemia patients with active disease

Abstract: In 26 myeloid and lymphoid acute leukemia patients at presentation the capacity to generate interleukin-2 (IL-2)-induced lymphokine-activated killer (LAK) cells effective against the natural killer (NK)-resistant Raji cell line, as well as the susceptibility of the blasts to normal peripheral blood (PB) LAK cells and to autologous LAK effectors was analyzed. The overall PB LAK activity against Raji cells was significantly lower in acute leukemia patients compared with normal controls (mean, 1,473 +/- 971 SD LU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…While the integrity of cytotoxic lymphocytes is pivotally important for patients with AML – in particular in protecting patients in complete remission against leukaemic relapses – these lymphocytes are frequently incapable of eliminating arising or residual leukaemic cells. Thus, several investigators have reported a reduction of the anti‐leukaemic activity of lymphocytes recovered from AML patients (Hersh et al , 1971; Foa et al , 1991; Tajima et al , 1996; Orleans‐Lindsay et al , 2001; Costello et al , 2002). A plethora of mechanisms have been proposed to account for the dysfunctional anti‐leukaemic lymphocytes in AML, including the production of T‐ and NK cell‐inhibitory factors by AML blasts (Buggins et al , 2001), a deficient expression of NK cell receptors on AML blasts (Nowbakht et al , 2005), deficient expression of the CD3 ζ transduction molecule (Buggins et al , 1998), inhibition of anti‐leukaemic lymphocytes by MPs (Pizzolo et al , 1988), an impaired stimulatory interaction between the CD28 antigen expressed by T cells and contact antigens on AML blasts (Notter et al , 2001), and a propensity of dormant AML blasts to resist cytotoxic T‐lymphocyte‐mediated killing (Saudemont & Quesnel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…While the integrity of cytotoxic lymphocytes is pivotally important for patients with AML – in particular in protecting patients in complete remission against leukaemic relapses – these lymphocytes are frequently incapable of eliminating arising or residual leukaemic cells. Thus, several investigators have reported a reduction of the anti‐leukaemic activity of lymphocytes recovered from AML patients (Hersh et al , 1971; Foa et al , 1991; Tajima et al , 1996; Orleans‐Lindsay et al , 2001; Costello et al , 2002). A plethora of mechanisms have been proposed to account for the dysfunctional anti‐leukaemic lymphocytes in AML, including the production of T‐ and NK cell‐inhibitory factors by AML blasts (Buggins et al , 2001), a deficient expression of NK cell receptors on AML blasts (Nowbakht et al , 2005), deficient expression of the CD3 ζ transduction molecule (Buggins et al , 1998), inhibition of anti‐leukaemic lymphocytes by MPs (Pizzolo et al , 1988), an impaired stimulatory interaction between the CD28 antigen expressed by T cells and contact antigens on AML blasts (Notter et al , 2001), and a propensity of dormant AML blasts to resist cytotoxic T‐lymphocyte‐mediated killing (Saudemont & Quesnel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…First CR would be an appropriate setting for IL‐2 therapy if a status of minimal residual disease is required, and blast cells at this stage probably are most likely to be sensitive to immune‐mediated cytotoxicity 9. Only a few patients have been reported in the literature receiving IL‐2 maintenance in first remission outside of a BMT setting (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer (NK) cell activity is deficient in patients with acute leukemia, but this deficiency frequently is corrected upon achievement of CR 9. Interleukin‐2 (IL‐2) stimulates NK cell activity 10.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that as many as 70–80% of AML patients in CR will eventually relapse implies that the host’s immune system is frequently incapable of eliminating arising or residual leukaemic cells. Several investigators have demonstrated that lymphocytes recovered from AML patients are commonly dysfunctional [36–40]. A plethora of mechanisms have been proposed to account for the dysfunction of anti‐leukaemic lymphocytes in AML, including but not limited to the production of T‐ and NK cell‐inhibitory factors by AML blasts [41], a deficient expression of NK cell receptors [40], inhibition of anti‐leukaemic lymphocytes by mononuclear myeloid cells [16], an impaired stimulatory interaction between the CD28 antigen expressed by T cells and contact antigens on AML blasts [42], and Fas ligand‐induced apoptosis of T cells [43].…”
Section: Mechanisms Of T Cell and Nk Cell Inactivation: Implications mentioning
confidence: 99%